Advanced Techniques in Web Intelligence-2 Web User Browsing Behaviour and Preference Analysis - Vels̀quez, Juan D.; Palade, Vasile.; Jain, Lakhmi C. (Studies in Computational Intelligence, 2013)
This research volume focuses on analyzing the web user browsing behaviour and preferences in traditional web-based environments, social networks and web 2.0 applications, by using advanced techniques in data acquisition, data processing, pattern extraction and cognitive science for modeling the human actions. The book is directed to graduate students, researchers/scientists and engineers interested in updating their knowledge with the recent trends in web user analysis, for developing the next generation of web-based systems and applications.